2013
DOI: 10.1371/journal.pone.0082601
|View full text |Cite
|
Sign up to set email alerts
|

Changing Trends in the Prevalence of Shigella Species: Emergence of Multi-Drug Resistant Shigella sonnei Biotype g in Bangladesh

Abstract: Shigellosis, caused by Shigella species, is a major public health problem in Bangladesh. To determine the prevalence and distribution of different Shigella species, we analyzed 10,827 Shigella isolates from patients between 2001 and 2011. S. flexneri was the predominant species isolated throughout the period. However, the prevalence of S. flexneri decreased from 65.7% in 2001 to 47% in 2011, whereas the prevalence of S. sonnei increased from 7.2% in 2001 to 25% in 2011. S. boydii and S. dysenteriae accounted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
75
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 47 publications
7
75
1
3
Order By: Relevance
“…Authors in Taiwan, Bangladesh, Bhutan, Iran and Argentina observed similarities above 70 % among strains of S. sonnei using PFGE (Lee et al, 2003;Ud-Din et al, 2013;Ruekit et al, 2014;Farshad et al, 2015). These data corroborate those of the present study because the strains of the PFGE-A and PFGE-B groups had a similarity above 70.8 % between each other (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Authors in Taiwan, Bangladesh, Bhutan, Iran and Argentina observed similarities above 70 % among strains of S. sonnei using PFGE (Lee et al, 2003;Ud-Din et al, 2013;Ruekit et al, 2014;Farshad et al, 2015). These data corroborate those of the present study because the strains of the PFGE-A and PFGE-B groups had a similarity above 70.8 % between each other (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…In Bangladesh the resistance of Shigella sonnei to ciprofloxacin is increasing dramatically. It has been shown that in 2007, 10% of the strains were resistant to ciprofloxacin, and by 2011, the resistant strains peaked to 70% [1]. We also observed the similar trend i.e.…”
Section: Discussionsupporting
confidence: 84%
“…Unlike some of the other U.S. isolates deposited as a part of GenomeTrakr project, CA isolates did not cluster with European FQ-resistant isolates and likely represent a direct introduction event. As S. sonnei is becoming more common in developing countries (13, 14), as in many of the countries in South and Southeast Asia, it could further increase the risk of clonal expansion and global dissemination of FQ-resistant strains of S. sonnei .…”
Section: Discussionmentioning
confidence: 99%
“…Infections caused by S. boydii are relatively uncommon worldwide (12). There is an emerging global trend of S. sonnei replacing S. flexneri in areas of developing countries undergoing economic growth and improvement in sanitation, such as Vietnam (13), and Bangladesh (14). …”
Section: Introductionmentioning
confidence: 99%